i-SMARTS: Digitalization of Agrotechnopreneurship-Based MSME Development to Support Acceleration of East Java Economic Recovery in The Middle of The Covid-19 Pandemic - Silvia Mayningrum; Kamil Muhtadi (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2021)
The COVID-19 pandemic has had a negative impact on MSMEs in East Java Province, one of which experienced a decline in sales and customers due to the PSBB and PPKM policies. The policy requires all MSMEs to carry out business activities online, but not all MSME actors are able to carry it out. The aims of this study were to analyze the perceptions of MSME actors in East Java during the COVID-19 pandemic, to find out the agrotechnopreneurship-based i-SMARTS system model, and to analyze the impact of the i-SMARTS system on the income of MSME actors and Gross Regional Domestic Product of East Java. The method of determining the sample in this study used the convenience sampling method with a total sample of 30 respondents. The data analysis used in this study were a Likert scale, systems approach analysis, and simulative descriptive analysis. The results showed that the perception of MSME actors towards business activities during the COVID-19 pandemic was 73.2% which means that MSME business activities are still less effective and as many as 78.9% of respondents really need an institution that oversees MSMEs in East Java. i-SMARTS as an agrotechnopreneurship-based institution offers various facilities to assist MSME actors in increasing their income during the COVID-19 pandemic. The application of i-SMARTS based on agrotechnopreneurship was able to increase the income of MSME actors during the COVID-19 pandemic from IDR 5,571,666.67 to IDR 9,750,416.67 and had implications for an increase in Gross Regional Domestic Product of East Java. i-SMARTS is the right solution strategy to overcome all the problems faced by MSME actors during the COVID-19 pandemic and develop the MSME sector to support the acceleration of East Java’s economic recovery.